Prevalence and Risk Factors of Head Lice Among Schoolchildren in Kirkuk: Prevalensi dan Faktor Risiko Kutu Rambut di Kalangan Anak Sekolah di Kirkuk - Aziz, Fatema W. Abdul (Academia Open, 2025)
Background: Head lice (Pediculus humanus capitis) are common, blood-sucking ectoparasites that infest the human scalp, with significant public health relevance, particularly among school-aged children. Specific Background: These wingless insects, belonging to the order Phthiraptera, are highly transmissible in dense environments such as schools. Knowledge Gap: Despite global awareness, there is limited region-specific data on infestation prevalence and contributing factors in northern Iraq, particularly in Kirkuk City. Aim: This study aimed to determine the prevalence of pediculosis and identify associated sociodemographic and behavioral risk factors among schoolchildren in Kirkuk. Results: Visual inspections of 300 pupils from five schools revealed an overall infestation rate of 10.3%, with higher prevalence among females (13%) compared to males (4.44%). Children aged 6–12 and those in lower educational levels exhibited significantly higher infestation rates. Behaviors such as sharing combs and clothing were also associated. Novelty: This is the first extended surveillance-based study in Kirkuk that combined clinical inspection with behavioral questionnaires over a full year. Implications: Findings underscore the need for enhanced school-based health education, early detection, and hygiene practices to mitigate the spread of pediculosis. Regional strategies should incorporate community involvement and consistent provision of preventive treatments. Highlights: High-risk group: Females and children aged 6–12 most affected. Transmission factors: Sharing combs, clothes, and beds increases risk. Prevention focus: Health education and treatment programs are essential. Keywords: Pediculosis, Head lice, Schoolchildren, Prevalence, Public health